Children with severe multiple disabilities: review of foreign literature - Vetrova, M.A.; Vetrov, A.O. (Sovremennaâ Zarubežnaâ Psihologiâ, 2022)
This article is a review of foreign studies devoted to the organization of psychological and pedagogical assistance to preschool children with severe multiple disorders (SMD). Retrospective data and modern ideas about this nosological group in Russia are presented. In parallel, modern ideas about it in other countries, current research in the field of diagnostics, organization of education, upbringing and social rehabilitation of preschool children with severe disabilities are considered. Among the measures to address issues of development of the socio-communicative sphere, the effectiveness of measures aimed at teaching preschoolers and their immediate environment to use the means of alternative and additional communication, ensuring accessible and developing communication was noted. Among the features of the development and implementation of special educational programs, the importance of a team approach, cooperation with the family and orientation towards teaching disabled child vital skills are highlighted. When comparing the subject of discussion with domestic theory and practice, the similarity of terminological contradictions was noted, as well as the recognition and use in our country of many foreign methods and approaches. Данная статья — обзор зарубежных исследований по проблеме организации психолого-педагогической помощи дошкольникам с тяжелыми множественными нарушениями (ТМНР). Приведены ретроспективные данные и современные представления об этой нозологической группе в России. Параллельно рассмотрены современные представления о ней в других странах, актуальные исследования в области диагностики, организации обучения, воспитания, социальной реабилитации детей дошкольного возраста с тяжелой инвалидностью. Среди мер по решению вопросов развития социально-коммуникативной сферы отмечена эффективность мероприятий, направленных на обучение дошкольников и их ближайшего окружения использованию средств альтернативной и дополнительной коммуникации, обеспечению доступного и развивающего общения. Среди особенностей разработки и реализации специальных учебных программ выделены значимость командного подхода, сотрудничества с семьей и ориентации на обучение ребенка-инвалида жизненно необходимым навыкам. При сравнении предмета обсуждения с отечественной теорией и практикой отмечены сходство терминологических противоречий, а также признанность и использование в нашей стране многих зарубежных методов и подходов.